Incidence of Linguatula serrata nymphs and pathological lesions of mesenteric lymph nodes in cattle from Urmia, Iran - M. Tavassoli (Bulgarian Journal of Veterinary Medicine, 2018)
This study was aimed to determine the infection rates of mesenteric lymph nodes (MLNs) with Lin-guatula serrata nymphs and their pathological lesions. From November 2012 to June 2013, the MLNs of 104 cattle were randomly sampled in Urmia slaughterhouse, northwestern Iran. They were examined macroscopically and histopathologically. The infected and non-infected lymph nodes were processed for histopathology. They were examined under light microscope and observations were recorded. The results indicated that out of 104 sampled cattle, 63 (60.57%) were infected. Macro-scopic examination revealed that the infected lymph nodes were swollen and dark, with rubbery con-sistency, some with subcapsular haemorrhages on cutting. The mean number of counted lymph node follicles in the nodes from healthy cattle at random microscopic levels was 18±2.8 (range 15–23), compared to 48.9±3.7 (range 44–57) in the infected nodes. Because L. serrata is a zoonotic parasite, preventive measures should be adopted to break the parasite’s cycle and minimise the risk of infection in both humans and other animals.